Influence of a Standard Heat Treatment on the Microstructure and Properties of Inconel X-750 Produced by Laser Powder Bed Fusion - Volpato, Guilherme Maziero; Pereira, Adriano de Souza Pinto; Neumeier, Steffen; Hotza, Dachamir; Göken, Mathias; Tetzlaff, Ulrich; Fredel, Márcio Celso (Advanced Engineering Materials, 2025)
The production of nickel-base superalloys through powder bed fusion using a laser beam (PBF-LB) offers a promising method for reducing the cost of aeronautical components, especially those with complex geometries. However, when these materials are processed using PBF-LB, the standard heat treatments developed for conventional manufacturing routes do not consistently yield predictable microstructures or mechanical properties. Thus, this study analyzes how PBF-LB affects the microstructure and mechanical behavior of Inconel alloy X-750 when compared to a hot-rolled counterpart after undergoing a standard precipitation-hardening heat treatment (solution annealing, stabilization, and precipitation). Microstructure is examined using analytical electron microscopy and high-energy X-ray diffraction, while mechanical behavior is assessed through microhardness. Significant differences between both manufacturing routes are detected, so that PBF-LB processing led to an increase in grain size, anisotropy, fraction of low-angle grain boundaries, mean angle of misorientation, and dislocation density. Moreover, PBF-LB promoted the formation of γ′-Ni3(Al,Ti) and η-Ni3Ti phases during solution annealing and stabilization, respectively. Notably, the formation of γ′ contributes to an anomalous microhardness increase observed between these steps. These findings suggest that PBF-LB may inhibit recrystallization and facilitate precipitation during heat treatment, thereby affecting the performance of components produced using this technology.
CRIS-Team Scopus Importer:2025-06-06
Keywords: additive manufacturing; eta phase; Inconel; laser powder bed fusion; selective laser melting